2021
DOI: 10.1162/jocn_a_01728
|View full text |Cite
|
Sign up to set email alerts
|

Neural Correlates of Hand–Object Congruency Effects during Action Planning

Abstract: Selecting hand actions to manipulate an object is affected both by perceptual factors and by action goals. Affordances may contribute to “stimulus–response” congruency effects driven by habitual actions to an object. In previous studies, we have demonstrated an influence of the congruency between hand and object orientations on response times when reaching to turn an object, such as a cup. In this study, we investigated how the representation of hand postures triggered by planning to turn a cup was influenced … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 94 publications
0
6
0
Order By: Relevance
“…10,46,92 Of note, the lateral pathway connecting the superior temporal sulcus to ventral prefrontal and anterior cingulate areas would be relevant in social cognition subcomponents of this task. 46,82,83 Lesion symptom mapping studies for object use deficits have identified lesions within the ventro-dorsal affordance and ventral streams, involving object recognition 63,70,99 and body-schema or posture representation areas, [100][101][102] respectively. These areas include ventral premotor cortex, as well as the inferior parietal cortex.…”
Section: Occurrencementioning
confidence: 99%
See 2 more Smart Citations
“…10,46,92 Of note, the lateral pathway connecting the superior temporal sulcus to ventral prefrontal and anterior cingulate areas would be relevant in social cognition subcomponents of this task. 46,82,83 Lesion symptom mapping studies for object use deficits have identified lesions within the ventro-dorsal affordance and ventral streams, involving object recognition 63,70,99 and body-schema or posture representation areas, [100][101][102] respectively. These areas include ventral premotor cortex, as well as the inferior parietal cortex.…”
Section: Occurrencementioning
confidence: 99%
“…The superior temporal sulcus is part of the body schema and pantomime network implicated in representing biological motion and other's actions, 10,46,84,104 whereas the inferotemporal area and adjacent inferior occipital lobe regions are thought to have a greater role in the representation of hand posture and handobject interactions. [100][101][102] There are projections from the superior temporal sulcus to the inferior parietal cortex, which is a relevant pathway for observing object-related actions 82,83 (part of this pathway is depicted schematically in Figure 2).…”
Section: Occurrencementioning
confidence: 99%
See 1 more Smart Citation
“…Neural correlates of affordance-incompatible action execution. To identify neural correlates that are activated more when executing affordance-incompatible actions compared to affordance-compatible actions [11,12], a model-free GLM analysis was conducted (GLM5). GLM5 included stick regressors representing the stimuli identities at the stimulus onsets, 2 regressors representing whether the affordance and response were compatible or not at the response onsets, and a parametric regressor of reward at the outcome onsets.…”
Section: Methodsmentioning
confidence: 99%
“…We first ascertained to what extent did the affordance properties of a stimulus influence response reaction times (RTs). We expected that choice of an action compatible with the dominant action affordance for an object would be associated with shorter RTs than choice of an affordance incompatible action regardless of the presence of ongoing value learning [10][11][12]. RTs were defined as the interval between the stimulus onset and initiation of movement, and were indeed found to be significantly shorter when making affordance-compatible actions compared to affordance-incompatible actions in both the behavioral and fMRI data even when participants were freely exploring the environment for finding the most rewarding hand gesture (Figs.…”
Section: Effects Of Affordance On Reaction Times and Action Selectionmentioning
confidence: 99%